Of Bumping and Bending: Foreign Universities' FDI Strategies in Malaysia - Marc Philipp Schulze (Tijdschrift voor economische en sociale geografie, 2021)
Universities from varying institutional and geographical contexts have increasingly invested in offshore subsidiaries in the Malaysian private higher education sector. Literature on transnational education policy and management as well as economic-geographic accounts of firms' transnationalisation or public service provision have not investigated foreign providers' direct investment and market access strategies in the higher education sector. This paper addresses these gaps, showing how and why foreign actors' investment and market involvement in Malaysia have changed. Empirical data is drawn from qualitative interviews and policy documents. The research reveals that foreign universities have strategically modified their business partnerships and bi-national accreditation to bypass and bend state regulation of market access as well as to restructure internal organisation and geographical configuration. The paper proposes conceptualising foreign higher education providers as transnationalising, reflexive networks within networks that respond to dynamic market access regulation by adopting firm-like investment strategies.
Keywords: 330; universities; FDI; market access; regulation; Malaysia